Contribution of Scalp Regions to Machine Learning-Based Classification of Dementia Utilizing Resting-State qEEG Signals [Corrigendum] - Simfukwe C; An SSA; Youn YC (Neuropsychiatric Disease and Treatment)
Simfukwe C, An SSA, Youn YC. Neuropsychiatr Dis Treat. 2024;20:2375—2389. The authors have advised that the funding statement on page 2387 is incorrect. The correct statement should read as follows. FundingThis research was supported by the Cooperative Research Program for Agriculture Science and Technology Development (Project No. PJ01712403) Rural Development Administration, Republic of Korea, and a basic science research program through the National Research Foundation of Korea (NRF) funded by the Ministry of Education (RS-2023-00251396 and 2021R1A6A1A03038996). The authors apologize for this error.